EFEKTIVITAS EXTRA VIRGIN COCONUT OIL DAN OLIVE OIL TERHADAP FUNGSI MEMORI DAN BELAJAR MENCIT - Gorga Menak Sihombing; Rizna Tyrani Rumanti; Decky Gunawan (NEURONA, 2019)
THE EFFECT OF EXTRA VIRGIN COCONUT OIL AND OLIVE OIL TOWARD MEMORY AND STUDY FUNCTION IN MICEABSTRACTIntroduction: Dementia is a neurodegenerative syndrome caused by chronic progressive abnormality and multiple malfunctions of the noble functions especially in memory and learning. Medium chain triglycerides (MCT) and polyphenol in extra virgin coconut oil (EVCO) and extra virgin olive oil (EVOO) can increase cognitive function.Aim: To discover the effect of extra virgin coconut oil (EVCO), extra virgin olive oil (EVOO) on increasing memory and learning ability of mice that are induced by aluminium chloride (AlCl3).Methods: A true experimental study was conducted using a completely randomized and comparative design. Experimental subjects were 24 mice, divided into 4 groups: K1 (negative control, aquades), K2 (AlCl3 + aquades), K3 (AlCl3 + EVCO 30mL/kg/day), and K4 (AlCl3 +EVOO 30mL/kg/day). Aluminium chloride was given for 15 days, then continued by EVCO and EVOO for 15 days. The dependent variable was recognition index (RI) with object recognition test post treatment. Data was analyzed using ANOVA, continued by LSD test with α=0.05.Results: Recognition index between K3 and both K1 and K2 showed a highly significant difference, and RI between K4 and both K1 and K2 also showed a highly significant difference. K4 was better in increasing RI compared with K3 with significant difference.Discussion: Extra virgin olive oil and EVOO improved the learning function and memory of mice induced by AlCl3. Extra virgin olive oil worked better than EVCO, because EVOO contains polyphenols that can work as neuro- inflammation, neurotoxicity and neuronal dysfunction inhibitors, while EVCO contains MCT as the main energy source when nerve damage occurs.Keywords: Dementia, extra virgin coconut oil (oleum cocos), extra virgin olive oil (oleum olivae), learning, memoryABSTRAKPendahuluan: Demensia adalah sindrom neurodegeneratif yang timbul karena adanya kelainan yang bersifat kronis dan progresif disertai dengan gangguan fungsi luhur multipel terutama pada memori dan belajar. Medium chain triglycerides (MCT) dan polifenol pada extra virgin coconut oil (EVCO) dan extra virgin olive oil (EVOO) dapat meningkatkan fungsi kognitif.Tujuan: Untuk mengetahui efek pemberian EVCO, EVOO, serta membandingkan keduanya dalam meningkatkan fungsi memori dan belajar mencit yang diinduksi aluminium klorida (AlCl3).Metode: Penelitian dengan desain studi eksperimental sungguhan menggunakan rancangan acak lengkap dan bersifat komparatif, dengan subjek penelitian 24 ekor mencit Swiss Webster yang dibagi menjadi 4 kelompok: K1 (kontrol negatif, akuades), K2 (AlCl3 +akuades), K3 (AlCl3 +EVCO 30mL/kgBB/hari), dan K4 (AlCl3 + EVOO 30mL/kgBB/hari). Aluminium klorida diberikan selama 15 hari, dilanjutkan dengan pemberian EVCO dan EVOO selama 15 hari. Variabel respons adalah indeks rekognisi (IR), dengan object recognition test setelah perlakuan. Analisis data dengan ANOVA dilanjutkan uji LSD dengan α=0,05.Hasil: Perbandingan IR K3 dengan K1 dan K2 memiliki perbedaan yang sangat bermakna, sedangkan K4 dengan K1 dan K2 memiliki perbedaan yang sangat bermakna. Kelompok 4 lebih baik dalam meningkatkan IR dibandingkan K3 dengan perbedaan bermakna.Diskusi: Extra virgin coconut oil dan EVOO meningkatkan fungsi belajar dan memori mencit yang diinduksi AlCl3. Extra virgin olive oil lebih baik dibandingkan EVOO, karena EVOO mengandung polifenol yang dapat bekerja sebagai penghambat neuroinflamasi, neurotoksisitas, dan disfungsi neuron, sedangkan EVCO mengandung MCT sebagai kandungan utama yang berperan sebagai sumber energi utama bila terjadi kerusakan saraf.Kata kunci: Belajar, demensia, extra virgin coconut oil (oleum cocos), extra virgin olive oil (oleum olivae), memori